Childhood immunization during the COVID-19 pandemic in Texas. Issue 25 (8th June 2021) - Nuzhath, Tasmiah; Ajayi, Kobi V.; Fan, Qiping; Hotez, Peter; Colwell, Brian; Callaghan, Timothy; Regan, Annette K.
Abstract: In 2020, the state of Texas implemented coronavirus disease 2019 (COVID-19) social distancing guidelines in order to prevent surges at Texas hospital emergency rooms and in intensive care units. As noted in other states, an unintended consequence of these activities was significant declines in childhood immunizations. After analyzing state-wide immunization register data for Texas, we observed a 47% relative decline in immunization rates between 2019 and 2020 among 5-month-olds and a 58% decline among 16-month-olds. We observed a small decline (5%) among 24-month-olds, and no decline in vaccines received at birth (Hepatitis B). Declines were larger in rural counties compared to urban. These declines are superimposed on increases in state vaccine exemptions over the last five years due to an aggressive anti-vaccine movement in Texas. There are concerns that continued declines in childhood immunization coverage due to COVID-19 could lead to co-endemics of measles and other vaccine preventable diseases.